2021
DOI: 10.1002/anie.202113370
|View full text |Cite
|
Sign up to set email alerts
|

Construction of NH‐Unprotected Spiropyrrolidines and Spiroisoindolines by [4+1] Cyclizations of γ‐Azidoboronic Acids with Cyclic N‐Sulfonylhydrazones

Abstract: The reactions of N-sulfonylhydrazones derived from cyclic ketones with g-azidopropylboronic acid and 2-(azidomethyl)phenylboronic acid give rise to spirocyclic pyrrolidines and spiroisoindolines,r espectively.T he reactions proceed without the need of any transition-metal catalyst through adomino process that comprises the formation of aCsp 3 -C and aCsp 3 -N bond of the former hydrazonic carbon. The scope of the reaction has been explored by the preparation of over 50 examples of NH-unprotected spirocyclic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…9 Our research group has successfully demonstrated the feasibility of this approach by capturing the boronic acid moiety via intramolecular cyclizations. Thus, we have developed cascade geminal C–C/C–C bond forming processes 10 as well as C–C/C–N cyclizations 11 (Scheme 1b) that have led to the development of new methods to synthesize quite complex Csp 3 -rich bicyclic and spirocyclic structures. Moreover, very recently, Merchant and Qin et al showed in a remarkable study, that the secondary and tertiary boronic acids which are obtained by reaction of N -sulfonylhydrazones of alkyl ketones and aldehydes with alkylboronic acids are not prone to undergo protodeboronation, and therefore can be efficiently trapped as pinacol boronates, providing a general method for the construction of these important synthetic intermediates with wide structural diversity (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…9 Our research group has successfully demonstrated the feasibility of this approach by capturing the boronic acid moiety via intramolecular cyclizations. Thus, we have developed cascade geminal C–C/C–C bond forming processes 10 as well as C–C/C–N cyclizations 11 (Scheme 1b) that have led to the development of new methods to synthesize quite complex Csp 3 -rich bicyclic and spirocyclic structures. Moreover, very recently, Merchant and Qin et al showed in a remarkable study, that the secondary and tertiary boronic acids which are obtained by reaction of N -sulfonylhydrazones of alkyl ketones and aldehydes with alkylboronic acids are not prone to undergo protodeboronation, and therefore can be efficiently trapped as pinacol boronates, providing a general method for the construction of these important synthetic intermediates with wide structural diversity (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, López et al reported the synthesis of spiropyrrolidines at the ketone group of 17α-methyltestosterone ( 50a ), cholest-4-en-3-one ( 50b ), 5α-cholestan-3-one ( 50c ), and 3-MOMO-estrone [ 34 ]. To construct the spiro heterocycle, an addition of p -toluenesulfonyl hydrazide to the carbonyl group of compounds 50a – c was carried out, resulting in the corresponding N -tosylhydrazones 51a – c .…”
Section: Reviewmentioning
confidence: 99%
“…Fused polycyclic cores containing hydro-azepine, azocine, or quinoline scaffolds are privileged skeletons in medicinal chemistry . In this context, we envisaged that N -sulfonyl hydrazides, by utilizing both the residual NH group and the NC bond, would be attractive precursors for the construction of cyclic, as well as acyclic, N -embedded cores . Since we have been focusing on developing allenes as useful partners in annulations, ,− , and ring expansion, we envisioned that combining the reactivity of allenoates with N -sulfonyl hydrazides should give viable access to N – N -annulated/fused systems.…”
mentioning
confidence: 99%